Inferência geográfica para delimitação de corredores ecológicos: um estudo de caso para a Mata Atlântica do município de Tibau do Sul/RN - Pereira, Vitor Hugo Campelo (2013)
The Atlantic Forest biome occupies much of the Atlantic coast of Brazil, in addition to portions of Paraguay and Argentina. Due mainly to its biodiversity which falls in the group of global hotspots, i.e., areas that have high priority for conservation. Although currently there are some available devices that assist in their protection in the course of the history of occupation and exploitation of the Brazilian territory, this biome has gone, and is still going through, an intense process of devastation, caused mainly by the pressure from economic activities, culminating in a significant reduction of its area and consequent fragmentation of the landscape, which brings with hosts a series of problems at various scales and aspects. As in most municipalities included in the reach area of the biome, the situation of forest fragmentation in Tibau do Sul / RN is quite critical, reflecting on a truly diverse landscape with broad typology of land uses. Among the alternatives aimed at the conservation of this biome include the creation of protected areas and the creation of ecological corridors, the latter being more efficient by connecting the remaining forests, increasing landscape connectivity, providing significant gains in relation to biodiversity. However, a major problem on implementation of Ecological Corridors projects is related to the selection of areas for this purpose, in this sense Geography can provide important contributions through the integrated study of landscape in the light of the geosystemic approach and the use of Geographical Information System (GIS) in order to permit assessment of reality having as a base the integration of ecological, biological and man-made aspects. Thus, this research aims to indicate potential areas and propose scenarios delimitation of Ecological Corridors in the municipality of Tibau do Sul / RN through Geographic Inference techniques in GIS platform. Therefore, the methodology adopted is based on the Geosystemic approach. From these elements were created 4 models to indicate potential areas for implementation of Ecological Corridors from the environmental perspective (potential erosion), socioeconomic (cover and land prices), legislative (areas protected by environmental legislation) and integrated (combination of environmental factors, socioeconomic and legislative), which in turn served as a basis for proposing scenarios aimed at this purpose. The results showed that all models can be quite useful in indicating potential areas for the establishment of ecological corridors, especially when based on an integrated approach between environmental and anthropogenic. The Corridors delimitation proposes shown may perform duties beyond the establishment of connectivity between fragments, since they also may have usefulness in controlling erosion and protecting fragile environments. Among the models developed, the integrated constituted itself as the best option because it enabled the interconnection of a larger number of fragments from a better use of the potentialities present in the landscape